Suboptimal Choice by Pigeons: Evidence that the Value of the Conditioned Reinforcer Rather than its Frequency Determines Choice. - Zentall, Thomas; Laude, Jennifer; Stagner, Jessica; Smith, Aaron (Psychological Record, 2015)
In an analog of human gambling, pigeons prefer a suboptimal alternative that infrequently provides a signal that is reliably associated with reinforcement over the more optimal alternative that yields more reinforcement. We hypothesized that pigeons are sensitive to the conditioned reinforcement that accrues to the stimulus associated with the greatest probability of reinforcement, independent of the frequency of its occurrence. In the present experiment we tested that hypothesis in a between groups design. For Group 50/75, choice of the suboptimal alternative 50 % of the time resulted in presentation of a stimulus that was always associated with reinforcement. For Group 25/75, choice of the suboptimal alternative 25 % of the time resulted in presentation of a stimulus that was always associated with reinforcement. For both groups, choice of the optimal alternative always resulted in presentation of a stimulus associated with 75 % reinforcement. In support of our hypothesis, both groups chose suboptimally and at the same rate. These results suggest that the conditioned reinforcing properties of the signal for reinforcement are acquired through its reliability as a signal for reinforcement and the frequency of its occurrence is of little importance.